Biological control in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Biological control: a sustainable solution to crop pest problems in Africa, edited by J S Yaninek and H R Herren IITA, Ibadan, NIGERIA